Clinical audit on type 2 diabetes Mellitus patients in a teaching primary care clinic in Kuantan, Pahang - Kamaluzaman, Qamarul Azwan; Musa, Noraini; Tg Ariff @ Tg Zainuddin, Tg Puteri Syarizan; Md Zin, Hezlin; Romali, Aini Laili; Abd Rahman, Mohd Aizuddin; Kamaruzaman, Nor Azam (2021)
Type 2 Diabetes Mellitus (DM) is an important risk factor for cardiovascular disease and microvascular complications. Patients with DM require ongoing evaluation and monitoring. Primary care serves as the first line of care and provides appropriate clinical management to delay T2DM complications, thus improve quality of life. This audit aims to describe patient’s profile and identify clinic performance in DM management at IIUM Family Health Clinic. Kuantan.